Geoflood Information Visualisor (GFIV) / Nor Aizam Adnan … [et al.] - Adnan, Nor Aizam; Ahmad Zahir, Ruzanna; Mohd Yusoff, Zaharah; Abdul Rasam, Abdul Rauf (Research Innovation Business Unit, 2014)
In general flooding is usually caused by heavy or continuous rainfall exceeding the absorptive capacity of soil and the flow capacity of rivers, streams and coastal areas. Flooding results in the inundation of an area by a rise of water by both dam failure or extreme rainfall durations and intensity in which life and properties in the affected area are under risk (Nyarko, 2002). Rainfall can produce very widespread surface flooding where water encounters dry ground and infiltrates, raising the groundwater volume (Gumbricht et al., 2004).This phenomenon has produced a large impact, which has destroyed livelihoods and altered environments, particularly in Asian countries (i.e. China, Bangladesh, India, Indonesia and Malaysia). Much research has been done and is still going on to understand flood characteristics and how to control flooding (Chan and Parker, 1996, Brivio et al., 2002; Adnan and Atkinson, 2011, Adnan et al., 2014)). Floods have caused such tremendous devastation which contribute to vulnerable losses and resulted in untold suffering of millions people in the world. Even today, floods lead all natural disaster in the number of people affected and in resultant of the economic losses, with these numbers rising at alarming rates. The aim of this study is to provide framework for flood hazard map identification, mapping and information related to flooding visualization from previous flooding event of the study area (i.e. Sg Segamat catchment) for the year 2006 flooding event. The objectives of this project is to i) to model flood hazard area of the Sg Segamat catchment using two dimensional (2D) hydrodynamic modelling and geospatial techniques data analysis and visualization, ii) to produce geospatial flood hazard inventory of area, types of land use, number of people (i.e. age, gender etc.) affected which can be displayed as statistical and visual informative results. The Infoworks RS, ArcGIS and ArcScene were used to determine the flooding behaviour technically and spatially. In this study the model represents the hydraulic phenomena in Sg Segamat catchment which occurred from 16-28 December 2006.The development of this hydrodynamic models consist of coupling one dimensional (1D) which is the focus area is for rivers and network system with the two dimensional (2D) which is on flood plains and overland flow path. The dynamic communication between models will greatly assist in predicting level of hazards within certain time steps. As a result of the whole research and analysing process the most affected area is at the downstream of Sungai Segamat. More than half of the flood area (57.9%) is located at the Mukim Gemereh which lies in the downstream of Sungai Segamat catchment. Other specific areas which are inundated by flood were Bandar Segamat, Kg. Chabong, Kg Tg Sengkawan, Taman Mega, Kg Jawa and Kg Padang Lalang. The validation of the results shows 61% of the total flood inundation area lies in the same area of the modelled flood. The most affected land use activity is agricultural activity which mainly affects the rubber plantation. The integration techniques between hydraulic modelling and geospatial data preparation and analysis were able to provide insightful framework for better flooding understanding and information in spatially manner. The flood information visualization derived from this study may be suitable to be used as tool especially, for water resources planning and management as well as by local authorities such as from Department of Irrigation and Drainage (DID) and also by Town, Country and Planning for better flooding decision making analysis related to flooding.